Analisis Faktor Penyebab Pending Klaim BPJS Kesehatan Rawat Inap Triwulan 1 Tahun 2026 di RSUD Kota Salatiga - Christina Ika Permatasari; Aries Widiyoko; Sinta Novratilova (Inovasi Kesehatan Global, 2026)
Pending claims in the National Health Insurance (JKN) reimbursement process can delay hospital cash flow and disrupt service management. This study aimed to analyze the factors causing pending inpatient BPJS Health claims at Salatiga Regional General Hospital using administrative, medical, coding, and 5M (Man, Method, Material, Machine, and Money) perspectives. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and document review involving inpatient claim officers, coders, and the Casemix unit. The findings revealed that pending claims were caused by incomplete administrative documents, including medical resumes, Participant Eligibility Letters (SEP), and supporting examination results. Medical factors included inappropriate hospitalization indications and incomplete clinical documentation, while coding factors involved inaccurate diagnosis and procedure coding due to non-specific diagnoses, incomplete supporting documents, and differences in interpretation between hospital coders and BPJS verifiers. Based on the 5M analysis, the material factor was identified as the dominant cause, particularly the incompleteness of medical record documentation required for claim verification. Strengthening documentation completeness, improving coordination among healthcare professionals, and conducting regular claim evaluations are expected to reduce pending claims and improve the efficiency of BPJS Health claim management